SUBLETHAL TOXIC EFFECTS OF CHLORPYRIFOS TO LIVER OF PUNTIUS CHOLA (HAMILTON-BUCHANAN) - VERMA, V. K.; SAXENA, AMITA (Journal of the Inland Fisheries Society of India, 2021)
Pesticides are indispensable in contemporary agriculture. Extensive demand for food production has increased the use of pesticides/ insecticides. They have, no doubt, increased crop yields by killing different types of pests, which are known to cause substantial or total crop damage. As a result, many other non-target organisms are accidentally poisoned. One of the non-target biological groups mostly affected by these pollutants is fish. Fishes are exposed to pesticides by many ways and the most common route is agricultural runoffs. The pesticides may finally find their way to the natural water bodies and affect the aquatic environment.